2004
DOI: 10.1111/j.1399-6576.2004.00528.x
|View full text |Cite
|
Sign up to set email alerts
|

Similar excitation after sevoflurane anaesthesia in young children given rectal morphine or midazolam as premedication

Abstract: In this study morphine for premedication in young children anaesthetized with sevoflurane was associated with similar postoperative and higher preoperative OPDS scores compared with midazolam. These findings indicate that substitution of morphine for midazolam is no useful way of reducing clinical excitation after sevoflurane anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Oral fentanyl at a dose of 15 lg kg -1 has been reported to cause preoperative vomiting [22], although lower doses seem to be a safe alternative to midazolam [23], despite a higher rate of PONV; other authors [24] have recently confirmed that oral fentanyl can reduce early postoperative agitation but increases both PONV and recovery times, thus limiting its clinical usefulness. Rectal morphine, when compared to midazolam, shows similar postoperative and higher preoperative discomfort and is not advisable as an alternative to midazolam [25]. Bibliographic data regarding the rectal administration of fentanyl are lacking; nevertheless, it is possible to suggest some hypotheses.…”
Section: Discussionmentioning
confidence: 97%
“…Oral fentanyl at a dose of 15 lg kg -1 has been reported to cause preoperative vomiting [22], although lower doses seem to be a safe alternative to midazolam [23], despite a higher rate of PONV; other authors [24] have recently confirmed that oral fentanyl can reduce early postoperative agitation but increases both PONV and recovery times, thus limiting its clinical usefulness. Rectal morphine, when compared to midazolam, shows similar postoperative and higher preoperative discomfort and is not advisable as an alternative to midazolam [25]. Bibliographic data regarding the rectal administration of fentanyl are lacking; nevertheless, it is possible to suggest some hypotheses.…”
Section: Discussionmentioning
confidence: 97%